Aggressive and unsportsmanlike behaviours in competitive sports: an analysis of related personal and environmental variables. - Pelegrín-Muñoz, Antonia; Serpa, Sidónio; Rosado, António (Anales de Psicología / Annals of Psychology, 2013)
This paper gives an analysis of personal and environmental variables related to aggressive and unsportsmanlike behaviours in a sample of Spanish sports competitors. We aim to: 1) ascertain how personality and expression variables relate to trait anger control and unsportsmanlike behaviors, in relation to men and women, age groups and type of sport; 2) identify and analyze the most maladjusted and the most adjusted profiles in a sample of sportsmen and women; 3) identify personality variables as predictors of aggressive and unsportsmanlike behaviours. Differences in gender, age and type of sport were appreciated in personality variables and in aggressive and unsportsmanlike behaviours. Men have better emotional adjustment (more behaviours of emotional stability, better self-esteem, self-confidence and leadership), and have worse social adjustment (fewer behaviours of tolerance, social skills and responsibility; more aggressive and unsportsmanlike behaviours). Women have better social adjustment (more behaviours of tolerance, understanding, adaptation, responsibility, discipline and sociability), and have worse emotional adjustment (greater anxiety). More aggressive and unsportsmanlike behaviours and greater emotional maladjustment were found in the youngest sportsmen and women. Aggressive and unsportsmanlike behaviours were more frequent in team sports. This study highlights personality variables as predictors of aggressive and unsportsmanlike behaviours.